Pentingnya Perencanaan Karir bagi Siswa Kelas IX di SMP Kamang Manggek dengan Menggunakan Bimbingan Klasikal - Sutrisno Sutrisno; Afrinaldi Afrinaldi; Efrienni Efrienni (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
N Career planning for students is an important thing to develop to support their desired goals. Classical guidance is a service activity that can be carried out in the classroom in the form of face-to-face meetings between teachers and students presented systematically for the development of certain competencies. The aim of this classical guidance activity is to improve career planning abilities for class IX students. Problems are solved in four stages of activity, namely planning, action, observation and reflection of activities. Data collection methods use interviews, observation, and a career planning ability scale. Based on the results of the activity, it was discovered that students experienced increased understanding after receiving material regarding career planning.